2019
DOI: 10.1891/1541-6577.33.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Nurses' Perceived Patient Safety Culture and Adverse Nurse Outcomes in Korea

Abstract: BackgroundHospital nurses are likely to be the first to observe patient safety issues in clinical settings, and thus it is important to include their views on patient safety culture. However, there are few studies addressing the influence of nurses' perceived patient safety culture on adverse nurse outcomes as quality of care.PurposeThis study was to identify the relationship between nurses' perceptions of patient safety culture and adverse nurse outcomes in Korea.MethodsThis cross-sectional study was included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This is a secondary analysis of existing data of 311 nurses of a tertiary hospital collected from March to May 2015, to examine patient safety culture and adverse nursing outcomes [ 39 ]. From the existing dataset, nurses under 35 were classified as early-career nurses and those aged 35 or older were classified as mid-career nurses [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is a secondary analysis of existing data of 311 nurses of a tertiary hospital collected from March to May 2015, to examine patient safety culture and adverse nursing outcomes [ 39 ]. From the existing dataset, nurses under 35 were classified as early-career nurses and those aged 35 or older were classified as mid-career nurses [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results affirmed that Filipino nurses displayed very high competency grade based on the standards set by the Philippine Board of Nursing, which considerably parallels the healthcare goal to ascertain that nurses provide acceptable, safe and quality patient care. While active patient involvement enhances patient safety outcomes, nurses have the likelihood of observing first-hand safety concerns in clinical areas, thus they have the accountability in preserving a safe hospital work environment on a regular basis to create a positive influence on patient safety (Arnetz et al, 2019;Bucknall et al, 2019;Choi et al, 2019;Christiansen et al, 2019;Yoong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At a particular note, nurses must always assess and achieve a safe working environment for patients to prevent errors related to medication and blood transfusion, falls, pressure sores and nosocomial infections (Arnetz et al, 2019;Ricklin et al, 2019;Shang et al, 2019). A high safety competency grade creates a positive influence on patients' overall safety due to enhanced teamwork, workshops and processes (Choi et al, 2019;Jin and Yi, 2019;Kahriman and Öztürk, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is because nurses are the professionals who have the closest contact with patients, who administer medications, provide important information and monitor the patient's condition. Studies have shown that when nurses fail to provide safe care to patients (Cho, Han, et al, 2020) or when the work environment is not configured in a way that allows nurses to provide safe care, patient safety is threatened (Choi et al, 2019; Hessels et al, 2019). Therefore, having the competency to provide safe nursing care is an essential ability for nurses, and is known as patient safety competency, which is defined as knowledge, skills and attitudes concerning patient safety, that are required for the provision of safe health care (Cronenwett et al, 2007; Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%